Information searching behavior among undergraduate student towards Online database usage - Zulkifli, Zahidah; Mat Surin, Ely Salwana; Salahuddin, Ashraf Ali; Mohammad Daud, Nur Hidayah (Institut Informatik Visual (IVI), Universiti Kebangsaan Malaysia, 2018)
Every year there are several online databases are subscribed by the library of International Islamic University Malaysia (IIUM) which allows around 15,625 undergraduate (UG) students to access and utilize the resources. Reported from IIUM library, up to the year 2015, 10 out of 53 online databases have been terminated from the subscription due to the decreasing and underutilized usage of online databases. This paper investigates the information seeking behavior (ISB) among those IIUM UG student who have access those subscribed resources and aims to discovers the relationship between elements of ISB among IIUM UG student and the impact of online database utilization. Data is collected through questionnaire which is constructed from the variables identified in this research objectives. 118 respondents from UG students have participated in the survey. The findings of this study will identify the gap between the ISB of IIUM UG students and subscribed online databases. It will help the librarian to encourage IIUM UG students to use online databases more in the future. Keywords: Information Seeking Behavior, Information Behavior, Online Database, Model Development.